Exercise for stroke prevention - Majoni, Melissa; Prior, Peter; Suskin, Neville (Henry Stewart Talks, 2019)
Risk factors for stroke, How exercise can reduce the risk of stroke, The benefits of exercise training and research evidence, Exercise behaviours among stroke patients, Success factors and barriers to success, Changing physical activity and exercise behaviour, Guidelines and recommendations, Contraindications to exercise testing and training